2007
DOI: 10.1021/ic701830m
|View full text |Cite
|
Sign up to set email alerts
|

Shorter Argentophilic Interaction than Aurophilic Interaction in a Pair of Dimeric {(NHC)MCl}2 (M = Ag, Au) Complexes Supported over a N/O-Functionalized N-Heterocyclic Carbene (NHC) Ligand

Abstract: Synthesis, structure, bonding, and photoluminescence studies of a pair of neutral dimeric silver and gold complexes of a N/O-functionalized N-heterocyclic carbene ligand exhibiting closed-shell d10...d10 argentophilic and aurophilic interactions, are reported. In particular, dimeric complexes of the type {[1-(benzyl)-3-(N-tert-butylacetamido)imidazol-2-ylidene]MCl}2 [M = Ag (2); Au (3)] displayed attractive metallophilic interaction in the form of a close ligand-unsupported metal...metal contact [3.1970(12) A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
84
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(94 citation statements)
references
References 81 publications
7
84
0
2
Order By: Relevance
“…[26] Stationary points were characterised by the right number of negative eigenvalues of the exact Hessian matrix. Gibbs free energies (at 25°C) are discussed throughout the text.…”
Section: Methodsmentioning
confidence: 99%
“…[26] Stationary points were characterised by the right number of negative eigenvalues of the exact Hessian matrix. Gibbs free energies (at 25°C) are discussed throughout the text.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the corresponding AuAu Wiberg Bond Index (0.14 and 0.15 for 2 and 6, respectively) are also similar and comparable to the values found for related (NHC)AuCl dimers. 15 Interestingly, the Second Order Perturbation Theory (SOPT) of the NBO method indicates that the aurophilic interaction is characterized by the donation of electron density from a doubly occupied d atomic orbital of one Au(I) to an empty p atomic orbital of the adjacent metal (see Figure 4). The associated SOPT energy computed for 2 and 6 is quite remarkable (DE (2) = -9.4 and -9.3 kcal/mol, respectively), thus reflecting the importance of these aurophilic interactions in the global stabilization of the novel Fischer type Au(I)-carbene complexes described herein.…”
Section: Scheme 1 Preparation Of Complexes 1-6mentioning
confidence: 99%
“…For instance, imidazole-and benzimidazole-based carbenes with short alkyl-chain substituents yield complexes of type B in the solid state [6,13], while those bearing long alkyl chains often result in complexes of type A 2 [14]. The exact geometry of this dimer A 2 can vary and a number of different structures has been reported, including the Ag 2 X 2 4-membered ring of 3 and 4 and a dimer formed by Ag-Ag interaction [8,15]. A study to determine the influence of the solvent showed that an increase in solvent polarity shifts the solution equilibrium from A to B for (IMes)AgCl (IMes = 1,3-bis(2,4,6-trimethylphenyl)imidazole-2-ylidene) [8].…”
Section: Structural Considerationsmentioning
confidence: 99%